The Influence Of Aqidah Akhlak Education In Increasing Character Values At Mi Nurul Islam Mirigambar - Laila Miftahhut Thoyyibah (STIT Attaqwa, 2023)
This research focuses on looking at the influence of moral education in improving character values at MI Nurul Islam Mirigambar. Ahklah faith education is one of the lessons that is very important to apply, especially in improving the quality of students' character in accordance with Islamic teachings. This research uses qualitative methods, and the data collection methods used in this research are observation, interviews and literature study. Meanwhile, data analysis includes data collection, data reduction, data display and data verification. The results of this research are divided into three things, first, the application of akhlah creed education by providing rules to achieve habits, with rules such as mandatory prayer, attendance on time, and others. Second, by implementing learning evaluations carried out by teachers on students, evaluations carried out by implementing mid-semester and final semester exams or by looking at students' abilities in their daily lives. In the evaluation carried out by the teacher, the aim is also to find solutions to student learning that is not achieved and understood when the teacher applies learning in class. Third, it shows the effectiveness of students in understanding the learning of moral beliefs, where students are able to understand the learning given by the teacher. The moral learning given by teachers to students turns out to be able to be applied in their daily lives, so that it has an impact on politeness and obedience in accordance with Islamic religious values